Analisis Implementasi Empat Pilar Corporate Social Responsibility (CSR) PT Pasangkayu dalam Meningkatkan Kesejahteraan Masyarakat di Sekitar Wilayah Operasional Perusahaan - Yorensia Resti; Muhammad Wandi Adriansa; Dina Hardianti; Indah Veronika; Nadia I Tala a; Wulandari Wulandari; Suci Handayani; Rahmawati Halim; Syarif Permana Salingkat; Richard F Labiro (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Corporate Social Responsibility (CSR) is a strategic instrument that connects corporate interests with community needs, especially for companies operating in resource extraction sectors. This study aims to analyze the implementation and effectiveness of CSR programs at PT Pasangkayu based on four main pillars: Education, Health, Economy, and Environment, as well as to identify their impact on community welfare in the operational area. This research employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with 19 informants, field observations, and documentation studies. The results show that PT Pasangkayu has consistently and structurally implemented its four-pillar CSR program in Martajaya Village, Pasangkayu Regency, West Sulawesi. The Education pillar is implemented through scholarships for 120 students per year and school infrastructure development. The Health pillar is realized through integrated health service programs, stunting prevention achieving a 12% reduction over two years, and provision of health facilities. The Economy pillar is carried out through the empowerment of 85 active SMEs and entrepreneurship training programs that increase community income by 25-30%. The Environment pillar encompasses annual reforestation of 10,000 seedlings, waste management, and natural resource conservation. Analysis using Stakeholder Theory, Triple Bottom Line, and the UN Sustainable Development Goals (SDGs) framework reveals that the four-pillar CSR implementation contributes significantly to sustainable community development. However, aspects of program sustainability, independent monitoring capacity, and community participation in program design still require enhancement.